2007
DOI: 10.1097/01.sla.0000250428.46656.7e
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in Colon Cancer

Abstract: The contribution of SLNB to conventional nodal staging of colon cancer patients is still unspecified. Technical problems have to be resolved before a definite conclusion can be drawn in this regard. However, SLNB identifies about one fourth of stage II patients to reveal MM/ITC in lymph nodes. Further studies must clarify the clinical impact of these findings in terms of prognosis and the indication of adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
85
4
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 28 publications
11
85
4
1
Order By: Relevance
“…In the two studies (n ¼ 25, 57) that used both radiocolloid and blue dye, the identification rate was 88% and 98% and the false negative rate was 45% and 17% [51]. A recent study that used blue dye only to identify the sentinel node found that a high false negative rate was associated with a higher body mass index (>24 kg/m 2 ) [53]. In addition, experience of the unit (<22 cases vs. >22 cases) is also associated with sentinel node identification rate [53], mirroring the melanoma [54] and breast cancer experience [55].…”
Section: Lymphatic Mapping and Ultrastaging Lymph Nodes In Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In the two studies (n ¼ 25, 57) that used both radiocolloid and blue dye, the identification rate was 88% and 98% and the false negative rate was 45% and 17% [51]. A recent study that used blue dye only to identify the sentinel node found that a high false negative rate was associated with a higher body mass index (>24 kg/m 2 ) [53]. In addition, experience of the unit (<22 cases vs. >22 cases) is also associated with sentinel node identification rate [53], mirroring the melanoma [54] and breast cancer experience [55].…”
Section: Lymphatic Mapping and Ultrastaging Lymph Nodes In Colon Cancermentioning
confidence: 99%
“…A recent study that used blue dye only to identify the sentinel node found that a high false negative rate was associated with a higher body mass index (>24 kg/m 2 ) [53]. In addition, experience of the unit (<22 cases vs. >22 cases) is also associated with sentinel node identification rate [53], mirroring the melanoma [54] and breast cancer experience [55]. Finally, aberrant lymphatic drainage or drainage to a lymph node in an area outside of the standard lymphadenectomy was most commonly to nodes located deep at the base of the mesentery and occurred 0-36% of the time [51].…”
Section: Lymphatic Mapping and Ultrastaging Lymph Nodes In Colon Cancermentioning
confidence: 99%
“…FI may offer better tissue contrast, facilitating detection in deep anatomic regions such as the abdomen, and is easy and safe to perform (13,14,17). Furthermore, ICG-FI is not influenced by the patient's BMI nor by lymphatic invasion, as has been shown for conventional methods, and has been shown to increase SLN detection in comparison with standard techniques (16,18). Although the ex vivo blue dye technique in SLN detection in CRC is well documented in the literature and has been demonstrated to be as effective and sensitive as the in vivo technique (19,20), no study has yet evaluated the role of ICG-FI using the ex vivo technique for SLN detection.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, in advanced disease, SN study is less useful as patients will receive adjuvant chemotherapy anyway. In a recent multi-centric trial, a cut-off level of 22 patients was defined to increase detection rate from 76.4% to 91.0% [43].…”
Section: Discussionmentioning
confidence: 99%